2018
DOI: 10.1111/jpn.12883
|View full text |Cite|
|
Sign up to set email alerts
|

An impact of Deoxynivalenol produced by Fusarium graminearum on broiler chickens

Abstract: Deoxynivalenol (DON) is a major mycotoxin from the trichothecene family of mycotoxins produced by Fusarium fungi that cause disease in grains. Food and feed contaminated with DON cause a variety of adverse health effects in humans and farm animals. However, the fermentation conditions of DON for toxicological study remain to be optimised. Deoxynivalenol levels were increased in a constant temperature of 20°C after fermentation for 7 and 14 days compared with cycling temperatures between 10-20°C and 15-20°C. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
(37 reference statements)
1
22
0
1
Order By: Relevance
“…Growth performance parameters of broiler chickens were not affected by DON guidance value (5 mg/kg) inclusion in experimental groups in present study. Likewise, lack of effect of DON at 5 mg/kg in feed on body weight gain, feed intake and feed conversion ratio was reported by researchers [ 22 , 23 ]. Even at 10 mg/kg tested in broiler diets, body weight, bodyweight gain, feed intake, and feed conversion ratio were not adversely affected for 35 d [ 7 , 8 ] and for 42 d [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Growth performance parameters of broiler chickens were not affected by DON guidance value (5 mg/kg) inclusion in experimental groups in present study. Likewise, lack of effect of DON at 5 mg/kg in feed on body weight gain, feed intake and feed conversion ratio was reported by researchers [ 22 , 23 ]. Even at 10 mg/kg tested in broiler diets, body weight, bodyweight gain, feed intake, and feed conversion ratio were not adversely affected for 35 d [ 7 , 8 ] and for 42 d [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 79%
“…It was reported that DON could reduce villus height, which was explained by villus contraction and resulted in nutrient transport and utilization impairment and, therefore, could impair zootechnical parameters [ 23 , 37 ]. However, in the current study, this decrease did not reach statistical significance, probably due to the difference of number of samples between treatments.…”
Section: Discussionmentioning
confidence: 99%
“…According to the procedures described by Yu et al. (2018) , DON was manufactured by inoculating rice with Fusarium graminearum ACCC 37687 and then was prepared into powder.…”
Section: Methodsmentioning
confidence: 99%
“…Trichothecenes, as T-2 toxin (Type A) and deoxynivalenol (DON), are produced by Fusarium graminearum and their intoxication cause decrease absorption of glucose [76], and the reduction of villus height and ratio of villus height:crypt depth in broilers [77]. Also, a pro-inflammtory response in the small intestine was observed with the consumption of DON in swine, murine and human's studies [78][79][80].…”
Section: Mycotoxinsmentioning
confidence: 99%